The effectiveness of occupational therapy for mental health disorders in primary care: A systematic review. (April 2022) - Daaleman, Claire E; Wright, Sarah T; Daaleman, Timothy P
Introduction: Occupational therapy (OT) has a rich history of integrating physical and mental health care services, however, there is a limited evidence base regarding the effectiveness of OT interventions for mental health disorders in primary care. Methods: A comprehensive systematic review was conducted from database inception through 31 January 2021. Eligible studies had to include: (1) an intervention that involved an occupational therapist in design and/or implementation; (2) a quantitative outcome assessing symptoms related to a mental health disorder; (3) a comparison group; and (4) primary care or community dwelling patients and/or primary care clinical settings. Results: The researchers identified five studies and there was heterogeneity in the OT interventions. There were no significant differences between intervention and control groups in depression symptoms at different time intervals. Several trials employed interventions that involved interprofessional team members, including OTs, to provide training in specific strategies that promoted functioning. Other studies utilized only OTs within the intervention arm. OT interventions demonstrated no significant difference in anxiety in one study, however, another indicated a reduction in symptoms. The overall risk of bias was considered low in three studies and unclear in two studies. Conclusion: There is limited evidence demonstrating the impact of OT interventions in primary care settings on quantitative outcomes measuring symptoms related to a mental health disorder. Given the heterogeneity of interventions and variation in reported findings, there is need for further pragmatic trials in this area.